A Quick Glance at Digital Watermarking in PACS - Syifak Izhar, Hisham; Liew, Siau-Chuin; Jasni, Mohamad Zain (Universiti Malaysia Pahang, 2012)
Nowadays PACS is used widely at hospitals and clinical departments globally. It able to help the clinical professionals doing diagnosis and smoothen the transmission process and storage of medical images. Since PACS handles thousands of crucial data in medical, security and authentication method is seen as very important in PACS. Digital watermarking is a field that receives many attentions and actively developed in researches lately. However, only a little of them had been tested in PACS. This paper surveys and reviews some researches about digital watermarking in PACS. This paper also provides some future perspective towards the improvement of application in PACS.